2015
DOI: 10.1111/evj.12497
|View full text |Cite
|
Sign up to set email alerts
|

Association between sesamoiditis, subclinical ultrasonographic suspensory ligament branch change and subsequent clinical injury in yearling Thoroughbreds

Abstract: The associations identified in this study highlight the importance of ultrasonographic examination of suspensory ligament branches in horses with PS sesamoiditis. This information should allow more accurate prognostic advice regarding potential SLBI development and also provide opportunities for intervention and prevention of clinical SLBI. THE SUMMARY IS AVAILABLE IN CHINESE - SEE SUPPORTING INFORMATION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Nonetheless, the consistent site and morphology of the lesions reported suggest pathogenetic commonality. The lesions are recognisable ultrasonographically but the radiological evidence of sesamoiditis, based principally on the number and nature of radial lucencies (vascular channels) reported in other SLB injuries in young racing Thoroughbreds [15,18] does not appear with a high level of frequency in this study (6 out of 32 limbs; 19%). In a post-mortem study of racing Thoroughbreds, SLB lesions were most common adjacent to the PSB and the authors considered the bone-ligament interface as susceptible to injury [16]; the results of the current study support this premise.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Nonetheless, the consistent site and morphology of the lesions reported suggest pathogenetic commonality. The lesions are recognisable ultrasonographically but the radiological evidence of sesamoiditis, based principally on the number and nature of radial lucencies (vascular channels) reported in other SLB injuries in young racing Thoroughbreds [15,18] does not appear with a high level of frequency in this study (6 out of 32 limbs; 19%). In a post-mortem study of racing Thoroughbreds, SLB lesions were most common adjacent to the PSB and the authors considered the bone-ligament interface as susceptible to injury [16]; the results of the current study support this premise.…”
Section: Discussionmentioning
confidence: 46%
“…Injuries to the SLB are common and seen in all type of horses . Subclinical ultrasonographic abnormalities have also been reported in horses which race on the flat [] and over fences . A post‐mortem study in Thoroughbred racehorses demonstrated correlation between forelimb SLB lesions and subsequent catastrophic (life ending) suspensory apparatus failure and fracture of the lateral condyle of the third metacarpal bone in the contralateral limb .…”
Section: Discussionmentioning
confidence: 99%
“…There were 10 Brown Swiss and one Holstein-Friesian dairy heifers with a mean age of 11 months (median, 10 months; range [8][9][10][11][12][13][14][15]. The caseload of lame cattle in the clinic during the study period consisted of 66% Brown Swiss, 27% Holstein-Friesian, and 7% other breeds.…”
Section: Re Su Ltsmentioning
confidence: 99%
“…1,2,13 In contrast to cattle, damage to the interosseus muscle-named suspensory ligament-is very common in horses and has been researched extensively. 12,14,15 Several categories of suspensory ligament injury are recognized in horses, including avulsion of the origin of the ligament, proximal suspensory desmitis, desmitis of the body or branches of the suspensory ligament, sesamoiditis, fracture of the proximal sesamoid bones, and desmitis of the distal sesamoidean ligaments. 16,17 Injuries causing complete rupture of the interosseus muscle/suspensory ligament are referred to as breakdown injuries.…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective study, Sarah Plevin and colleagues in the USA and UK investigated the associations between radiographic signs of sesamoiditis, ultrasonographic signs of suspensory ligament branch desmitis and subsequent clinical suspensory ligament branch injury (SLBI) .…”
Section: Suspensory Ligament Branch Injury Riskmentioning
confidence: 99%